PEMBELAJARAN IPAS BERBASIS ISU SAMPAH UNTUK MEMBENTUK KARAKTER PEDULI LINGKUNGAN SISWA SD BAROS 2 - Anna Maria Oktaviani; Yulia Agustina; Wina Ermawati (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The problem of waste constitutes an urgent global environmental and public health challenge, exacerbated by low levels of awareness. Therefore, the cultivation of eco-literacy and the development of environmentally caring character from an early age, particularly in elementary schools, are crucial. This study analyzes the effectiveness of Natural and Social Sciences (IPAS) learning based on wasterelated issues in shaping environmentally caring character among elementary school students. Using a Mixed Methods approach with a Sequential Explanatory design, the quantitative phase employed a quasi-experimental pre-test–post-test group design, which demonstrated a significant increase in students’ knowledge, attitudes, and environmentally responsible behaviors in the experimental group after the intervention. Students exhibited comprehensive understanding of waste, positive attitudes, and proactive behaviors such as waste sorting. The qualitative phase, conducted through a case study, confirmed that hands-on activities and indepth discussions facilitated conceptual understanding, fostered empathy, and internalized environmental care values. The role of teachers as facilitators and curriculum flexibility were identified as key factors for success. Thus, waste issue– based IPAS learning is highly effective in shaping environmentally caring character among elementary school students, recommending systematic integration of environmental issues and increased teacher support. The limitations of this study include issues of generalizability and the need for long-term evaluation.